Random Forest Algorithm to Investigate the Case of Acute Coronary Syndrome - Eka Pandu Cynthia; M. Afif Rizky A.; Alwis Nazir; Fadhilah Syafria (Ikatan Ahli Informatika Indonesia (IAII), 2021)
This paper explains the use of the Random Forest Algorithm to investigate the Case of Acute Coronary Syndrome (ACS). The objectives of this study are to review the evaluation of the use of data science techniques and machine learning algorithms in creating a model that can classify whether or not cases of acute coronary syndrome occur. The research method used in this study refers to the IBM Foundational Methodology for Data Science, include: i) inventorying dataset about ACS, ii) preprocessing for the data into four sub-processes, i.e. requirements, collection, understanding, and preparation, iii) determination of RFA, i.e. the